W. S. Thruston correspondence - Thruston, W. S.
ALS (Aberdeen) from Thruston to John Johnson, London, England, regarding a loan to settle an account.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Johnson, John, -- active 1790 -- Correspondence; Loans